Treat Menstrual Pain with Acupuncture Therapy - Setiawati, Rika; Priskila, Onny (Rifa'Institute, 2023)
Introduction: Menstrual pain, or dysmenorrhea, is pain or cramps in the lower abdomen that appear before or during menstruation. Dysmenorrhea can be mild or so severe that it interferes with activities. According to TCM, painful menstruation is caused by Qi and poor blood circulation caused by the clotting of cold and damp blood by pathogens. Objective: The purpose of this study was to see the effect of acupuncture therapy on reducing menstrual pain. Method: The research method used in the treatment of menstrual pain through acupuncture therapy is a qualitative research method with an interview and observation approach. In the process of this research, an observational approach was carried out because there were several respondents who experienced menstrual pain. Result and Discussion: Based on the results of the study, acupuncture therapy was carried out nine times with a quantity of three times a week, 5-7 days before the menstrual period, for three menstrual cycles, and the menstrual pain experienced by the client experienced a significant change. Conclusion: This is marked by a change in the pain scale from 7 to 1. In addition, the volume of menstruation also decreases, the color of the blood is lighter and not darker than before, and there are no clots.